The Influence of Sentence Element Awareness on English Language Proficiency Test’s Score - Viqi Ardaniah (MOZAIK HUMANIORA, 2014)
This study concerns the influence of sentence element awareness on the score of Grammar, Structure,and Written Expression (GSWE) in English Language Proficiency Test (ELPT). Some teaching methodsneed to be proposed to increase students’ awareness of sentence element. A class action methodwas used in this study, including planning, action, observation, and evaluation/reflection. For thispurpose, the study was conducted for 7 weeks involving the students taking Extensive English coursein the second semester of the academic year of 2013/2014. In the first week, the students were taughtEnglish simple sentence. In the next two weeks, students were taught English compound sentence.In the next two weeks, students were taught English complex sentences. In the last two weeks, theevaluation of GSWE was conducted. The results show that, first, the teaching method focusing onincreasing students’ awareness of English sentence elements was designed by comparing thoseelements to Indonesian sentence elements. Second, this teaching method design was able to increasestudents’ score of GSWE in ELPT, about 6.64%. Thus, teaching method focusing on increasingstudents’ awareness of English sentence elements can increase students’ score of GSWE in ELPT.Keywords: GSWE, sentence element, ELPT